PEMILIHAN KEPALA DAERAH DALAM PERSPEKTIF PERAN PENDIDIKAN KEWARGANEGARAAN Pemilihan kepala daerah dalam perspektif Pendidikan Kewarganegaraan - Cholisin Cholisin (Jurnal Civics: Media Kajian Kewarganegaraan)
Civic Education is an important component ofeducation of democracy, because itfosters citizen's participation within public daily life, in fonn ofpolitical participation, e.g. in election of head oflocal (llgencylprovence) guvemment-abbreviated into Pilkada for indirect election and Pilkadal for direct election by people. This paper focuses on implementation ofrole of Civic Education in context of Pilkadal  Through Civic Education, citizen is preparated to be rational voter, learn on democracy through democratic institution, e.g. Pilkadal Effectivity of Civic Education well be influenced by whether candidates contribute to strengthen rational-calctdatiue voting behavior or precisely foster emotional one. Pilkadal will be meaningful when it plays a role in fonn of the first So that; candidates should learn and then peform behavior according to what is striven in Civic Education. Finally, they could become a good "teacher". ofa political education through Pilkadal